Listeria monocytogenes Source Distribution Analysis Indicates Regional Heterogeneity and Ecological Niche Preference among Serotype 4b Clones - Sangmi Lee (American Society for Microbiology, 2018)
ABSTRACT Biodiversity analysis of the foodborne pathogen Listeria monocytogenes recently revealed four serotype 4b major hypervirulent clonal complexes (CCs), i.e., CC1, CC2, CC4, and CC6. Hypervirulence was indicated by overrepresentation of these clones, and serotype 4b as a whole, among human clinical isolates in comparison to food. However, data on potential source-dependent partitioning among serotype 4b clones in diverse regions are sparse. We analyzed a panel of 347 serotype 4b isolates, primarily from North America, to determine the distribution of clones in humans, other animals, food, and water. CC1, CC2, CC4, and CC6 predominated, but surprisingly, only three clones, i.e., CC2 and the singleton sequence types (STs) ST382 and ST639, exhibited significant source-dependent associations, with higher propensity for food (CC2) or water (ST382 and ST639) than other sources. Pairwise comparisons between human and food isolates identified CC4 as the only serotype 4b clone significantly overrepresented among human isolates. Our analysis also revealed several serotype 4b clones emerging in North America. Two such emerging clones, ST382 (implicated in several outbreaks since 2014) and ST639, were primarily encountered among human and water isolates. Findings suggest that in spite of the ubiquity of CC1, CC2, CC4, and CC6, regional heterogeneity in serotype 4b is substantially larger than previously surmised. Analysis of even large strain panels from one region may not adequately predict clones unique to, and emerging in, other areas. Serotype 4b clonal complexes may differ in ecological niche preference, suggesting the need to further elucidate reservoirs and vehicles, especially for emerging clones. IMPORTANCE In Listeria monocytogenes, serotype 4b strains are leading contributors to human disease, but intraserotype distributions among different sources and regions remain poorly elucidated. Analysis of 347 serotype 4b isolates from four different sources, mostly from North America, confirmed the overall predominance of the major clones CC1, CC2, CC4, and CC6 but found that only CC4 was significantly associated with human disease, while CC2 was significantly associated with food. Remarkably, several emerging clones were identified among human isolates from North America, with some of these also exhibiting a propensity for surface water. The latter included the singleton clones ST382, implicated in several outbreaks in the United States since 2014, and ST639. These clones were noticeably underrepresented among much larger panels from other regions. Though associated with North America for the time being, they may eventually become globally disseminated through the food trade or other venues.